The need for providing pharmaceutical care in geriatrics: A case study of diagnostic errors leading to medication-related problems in a patient treatment plan - Amna Shah; Atta Abbas Naqvi; Rizwan Ahmad (Archives of Global Professionals, 2016)
Background: Geriatric patients are more prone to suffer from medication related problems (MRPs). It may be due to comorbidity of chronic illnesses and/or number of medications prescribed to them as compared to other age groups. Illnesses are sometimes misdiagnosed or left undiagnosed due to aging. Pharmacists have the knowledge about the disease and medication therapy in geriatrics and can provide pharmaceutical care (PC) which can supplement decision making of physician, reduce MRPs and improve treatment outcomes. Introduction: This case study highlights the need to provide PC to geriatrics. A diabetic patient presented with hypoglycemia and suspected electrolyte imbalance to the emergency room (ER) and was prescribed a treatment plan which had the potential to result in MRPs. Case Presentation: An 80 years old male geriatric patient presented to ER with hypoglycemia. Past medical history revealed Type I DM and CABG. The treatment plan was more focused on resolving signs and symptoms for which no relevant laboratory and diagnostic tests were conducted. Medication therapy was prescribed to the patient on suspected diagnosis and more than one drug of the same therapeutic class was prescribed to the patient making him prone to suffer from MRPs. Conclusion: Incorporating a pharmacist driven PC can help prescribers in establishing diagnosis, selecting rational therapies for co morbidities in geriatrics. It can eliminate unnecessary drug therapy, concomitant use of similar drugs and also reduce the chances of MRPs thereby improving treatment outcomes.